Self-reported Vision Impairment and Subjective Well-being in Older Adults: A Longitudinal Mediation Analysis. (5th June 2019) - Xiang, Xiaoling; Freedman, Vicki A; Shah, Khushali; Hu, Rita X; Stagg, Brian C; Ehrlich, Joshua R
Abstract: Background: Vision impairment (VI) in older adults is associated with declines in well-being. However, the pathways through which poor vision leads to declines in well-being have not been well-described. The purpose of this study was to determine whether activity limitations and social participation restrictions mediate the impact of self-reported VI on subjective well-being. Methods: The National Health and Aging Trends Study (NHATS) is a nationally representative longitudinal study of Medicare beneficiaries 65 and older that includes detailed measures of the disablement process. A longitudinal mediation model was conceptualized linking self-reported VI and subjective well-being. Structural equation modeling was used to test the mediating effects of activity limitations and social participation restrictions while adjusting for relevant covariates. Results: The final sample included 5, 431 respondents. At baseline, 8.0% of Medicare beneficiaries had self-reported VI. Subjective well-being scores were significantly lower among respondents with self-reported VI (15.7; 95% confidence interval [CI]: 15.2, 16.2) compared with those without VI (17.6; 95% CI: 17.5, 17.7). Self-reported VI had a significant indirect effect on subjective well-being through limiting mobility (β = −0.04; 95% CI: −0.07, −0.03) and household activities (β = −0.05; 95% CI: −0.08, −0.03), but not self-care limitations (β = 0.0; 95% CI = 0.0, 0.0) or participation restrictions (β = 0.0; 95% CI = −0.01, 0.00). Total indirect effects from all mediation paths accounted for 42% of the effect of VI on well-being. Conclusions: Mobility and household activity limitations are significant mediators that explain a considerable portion of the impact of poor vision on well-being. Interventions to promote successful accommodation may result in greater overall well-being for older adults with poor vision.